Material Characterization and Machining Performance of Nodular Cast Iron - Granung, Emil; Werner, Angelica (My University, 2026)
The objective of this degree project was to investigate material and machining variations in nodular cast iron similar to EN-GJS-500-14, both between components from the same batch and within individual components. The aim was to examine the microstructure and properties of the material, as well as analyze the results of cutting tests, in order to minimize cutting tool consumption. To investigate the material variations, several analyses were performed, including preparation of samples, from which optical microscope images were acquired to analyze differences in graphite particles. Furthermore, some samples were etched to reveal the microstructure, after which hardness testing was performed. To evaluate machining performance, cutting tests were conducted using a turning machine. Tool wear and cutting forces were investigated, and scanning electron microscope (SEM) images of the cutting tools were taken to further analyze tool wear and material adhesion on the tool surface. Differences in graphite particles were observed across different axial positions within the same component, with higher values recorded along the edges compared to the central sections. Measured values included nodularity, particle density, and particle shape and size distribution. Cooling rate could explain all these variations as the major differences are evident along the outer edges and within thin sections of the components. The etched samples mainly consisted of ferrite, and the hardness of the samples corresponded to the nodularity. In machining, variations were also detected, where the maximum flank wear correlated with the nodularity and hardness of the material. Additionally, an increase in the resultant force showed similar correlation. SEM images revealed that the wear had not yet reached the cemented carbide and showed significant amounts of adhered material on the substrate.
Keywords: Nodular Cast Iron; Nodularity; Tool Wear; Graphite Particle; Machining